Contemporary ureteroscopic management of renal stones. (December 2016) - Proietti, S.; Knoll, T.; Giusti, G.
Abstract: The advancements in the endourological armamentarium and the evolution of ureteroscopes with the advent of fiberoptic first and then digital technology, the introduction of holmium laser lithotripters, together with the increasing number of requests for minimally invasive procedures has ameliorated outcomes, patients' safety and comfort, making the use of flexible ureteroscopy for urinary calculi increasingly attractive and widespread among urological community. Due to its high stone-free rates and low morbidity, flexible ureteroscopy has become a viable option for the treatment of renal stones. This review describes the contemporary ureteroscopic management of kidney stones. Highlights: Flexible ureteroscopy is an effective and safe procedure for the treatment of renal stones. Good results by fURS are possible only if a complex organization is established within a so called "stone center". Modern endourological armamentarium together dedicated OR schedule is essential. Choosing every time the best procedure for the stone and the patient (tailored surgery).